2018
DOI: 10.1101/395525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human antibody cocktail deploys multiple functions to confer pan-ebolavirus protection

Abstract: Africa and in its aftermath, the passive administration of monoclonal antibodies (mAbs) emerged as a promising treatment approach [1][2][3][4][5][6][7] . However, all antibody-based therapeutics currently in advanced development are specific for a single member of the Ebolavirus genus, Ebola virus (EBOV), and ineffective against divergent outbreak-causing ebolaviruses, including Bundibugyo virus (BDBV) and Sudan virus (SUDV) 2,3,5,7 . Here we advance MBP134, a cocktail of two broadly neutralizing human mAbs ta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Potent neutralization, broad reactivity, and protective capacity are desirable mAb features, which could be used to select leads for development as a monotherapy or cocktail. A cocktail might offer greater efficacy and resistance to viral escape (Corti et al, 2016;Keeffe et al, 2018;Wec et al, 2019), but the molecular and structural basis for the optimal combination of mAbs is ill-defined. Current mAb discovery approaches typically are focused on antibody variable fragment (Fv)-region-mediated biological functions of single isolated mAbs (e.g., binding and neutralization) or Fc-region-mediated effector functions (Walker and Burton, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Potent neutralization, broad reactivity, and protective capacity are desirable mAb features, which could be used to select leads for development as a monotherapy or cocktail. A cocktail might offer greater efficacy and resistance to viral escape (Corti et al, 2016;Keeffe et al, 2018;Wec et al, 2019), but the molecular and structural basis for the optimal combination of mAbs is ill-defined. Current mAb discovery approaches typically are focused on antibody variable fragment (Fv)-region-mediated biological functions of single isolated mAbs (e.g., binding and neutralization) or Fc-region-mediated effector functions (Walker and Burton, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One other investigational human mAb cocktail that demonstrated broad efficacy in NHPs, MBP134 AF , has been described (Bornholdt et al, 2019). MBP134 AF is comprised of antibody ADI-15878 and a derivative of antibody ADI-15946 (defined as ADI-23774), which was engineered to improve its specificity against SUDV GP (Wec et al, 2019). A comparison of our results to the reported activities of ADI-15946 or ADI-23774 (Wec et al, 2017) indicates a high potency for the homologous base-specific antibody rEBOV-515 that we describe.…”
Section: Discussionmentioning
confidence: 99%
“…The largest EVD epidemic to date occurred in 2013-2016 in West Africa with a total of 28,610 disease cases and 11,308 deaths reported (WHO, 2021), highlighting the urgent need for development of medical countermeasures. Monoclonal antibody (mAb) therapies have demonstrated safety and significant survival benefit in the treatment of acute EVD caused by EBOV in randomized controlled human trials (Gaudinski et al, 2019;Levine, 2019;Mulangu et al, 2019;Sivapalasingam et al, 2018), and several investigational human mAb treatments have been shown to reverse the advanced EVD in non-human primates caused by EBOV (Bornholdt et al, 2019;Corti et al, 2016;Gilchuk et al, 2020b;Pascal et al, 2018;Qiu et al, 2014), BDBV (Bornholdt et al, 2019;Gilchuk et al, 2018b), or SUDV (Bornholdt et al, 2019;Herbert et al, 2020). By 2020, two mAb-based therapeutics -ansuvimab-zykl (Ebanga) and atoltivimab + maftivimab + odesivimab-ebgn (Inmazeb) -have been developed and approved by the Food and Drug Administration (FDA) for clinical use (FDA, 2020a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Although breadth and potency are often opposing characteristics, we sought to engineer these bnAbs for improved neutralization potency against SARS-CoV-2, while also maintaining or improving neutralization breadth and potency against other SARS-related viruses. Because binding affinity and neutralization potency are generally well-correlated ( 14 ), we employed yeast-surface display technology to improve the binding affinities of three of the bnAbs (ADI-55688, ADI-55689, and ADI-56046) for a prefusion-stabilized SARS-CoV-2 S protein ( 11, 1517 ).…”
mentioning
confidence: 99%
“…Yeast display libraries were generated by introducing diversity into the heavy (HC)- and light-chain (LC) variable genes of ADI-55688, ADI-55689, and ADI-56046 through oligonucleotide-based mutagenesis and transformation into Saccharomyces cerevisiae by homologous recombination ( 15 ). Following four rounds of selection with a recombinant SARS-CoV-2 S1 protein, improved binding populations were sorted, and between 20 and 50 unique clones from each lineage were screened for binding to SARS-CoV-2 S ( 17 ) (Fig.…”
mentioning
confidence: 99%